First record of the non-native flowering plant Dichondra argentea (Convolvulaceae) in southern Europe and Italy: floristic, distributive and ecological notes - Ceschin, Simona; Raimondi, Dario; Mariani, Flaminia; Salerno, Giovanni (Phytotaxa, 2020)
Dichondra Forster & Forster (1776: 39) is one of the oldest genera included in the Convolvulaceae family and is estimated to include 15 species that are native to the tropical and warm temperate regions of Americas, New Zealand and Australia (Tharp & Johnston 1961, Staples et al. 2017, Delgado et al. 2018).